Assessment of Stock Market Liquidity and Efficiency: Evidence from an Emerging Country - Monga, Reema; Aggrawal, Deepti; Singh, Jagvinder (Organizations and Markets in Emerging Economies, 2023)
The study examines the market efficiency, multi-dimensions of liquidity, and their interconnectedness for the Emerging Indian Stock Market. In contrast to the extant literature, the current study involves testing the market liquidity considering multi-dimensions such as depth, breadth, immediacy, tightness, and resiliency. Second, the study used a battery of tests to determine efficiency, including the Ljung and Box, runs test, Bartel test, Variance ratio, and BDS tests. Furthermore, using five quintiles classified by market depth, the linkage of market efficiency and liquidity is also being investigated. The findings show that during the pandemic, the Indian stock market has been proven to be efficient, suggesting that there are no abnormal returns. Moreover, the research demonstrates that during the COVID-19 pandemic, large volumes of securities are traded quickly and at a lower price effect, but with higher trading costs for completing a market transaction. However, it is worth noting that increased liquidity equates to greater efficiency, while lower liquidity equates to inefficiency.
Keywords: COVID-19; market liquidity; efficiency; Indian stock market; multi-dimensional approach; country lockdown